Second Account Instagram Sebagai Representasi Identitas Virtual di Kalangan Mahasiswi Universitas Udayana - Putu Nita Kharisma Yanti; Ida Bagus Pujaastawa; Ida Bagus Oka Wedasantara (Institut Nalanda, 2025)
The presence of second accounts allows users greater freedom in expressing themselves compared to their main accounts. This study aims to describe the phenomenon of second account usage on Instagram in shaping the virtual identity of female students at Udayana University. The research focuses on the virtual identity constructed by students through their Instagram accounts and is analyzed using the Communication Theory of Identity. This research employs a qualitative descriptive method, with data collected through interviews, observation, and document analysis. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the virtual identity presented is shaped by both self-perception and the evaluations of others. As a result, the main account tends to be used strategically for managing self-image, while the second account allows for more flexible and authentic self-expression.